Fibrinogen mediates platelet-polymorphonuclear leukocyte cooperation during immune-complex glomerulonephritis in rats. - Wu, X (1994)
The metabolic and functional alterations which occur during the acute phase of nephrotoxic nephritis (NTN) in rats, a model of immune-mediated glomerulonephritis, result from a cooperative interaction between PMNs and platelets (PLTs). In consequence, we hypothesized that fibrinogen (Fg) might play a critical role in this process and, accordingly, we found that defibrination of animals decreased both the acute phase proteinuria in NTN (approximately 70%) as well as the influx of PLTs and PMNs into the glomerulus (approximately 40-50%). In contrast, blockade of the PLT Fg receptor, alpha IIb beta 3, with the RGD peptidomimetic SC-49992 decreased proteinuria (approximately 90%) without substantially altering the influx of PMNs or PLTs. Immunocytochemistry showed a marked increase in beta 3 integrin expression in inflamed glomeruli which was prevented either by PMN or PLT depletion before disease induction. FACS and immunocytochemical analysis of glomerular cell dissociates demonstrated that beta 3 integrin expression was predominantly on intraglomerular PLTs. In vitro, activated PLTs stimulated the PMN respiratory burst, an interaction which could be inhibited by Fg receptor blockade. In sum, acute NTN is accompanied by a marked increase in glomerular beta 3 integrin expression predominantly due to the influx of PLTs which localize to the glomerulus in a PMN-dependent fashion. Fg appears to serve a major role as a coactivating stimulus for PLT-PMNs in situ via alpha IIb beta 3, potentially mediating the PMN respiratory burst which contributes to proteinuria. Fg may also play a subsidiary role in PMN/PLT comigration.